STATE INTERVENTION IN SOCIO-ENVIRONMENTAL CONFLICTS IN PERU - Muñoz Muñoz, Delia (2023)
The increase in socio-environmental conflicts in Peru generates the perception, at the level of the population, of a lack of State intervention in the management of these conflicts and that this contributes to their reaching levels of violence. The objective of this study is to determine whether the scarce and untimely intervention of the State contributed to socio- environmental conflicts in Peru becoming violent, during the periods 2004 - 2020, through the methodology of the case study, with the review of 189 monthly reports of the Defensoría del Pueblo, published between October 2004 and July 2020, which evaluated the behavior of state entities in 99 socio-environmental conflicts reported as active in the Defensoría del Pueblo report of July 2020. On the basis of the information analyzed, it was possible to determine the participation of State entities in all the socio-environmental conflicts studied, fulfilling different roles and through institutions at its three levels (national, regional and local). The high percentage of conflicts that reach the level of violence and other evidence, allow us to conclude that the tate intervention is characterized by being reactive, inefficient and with little coordination between its different instances.